THE INTERRELATION OF FORCED EVICTION AND THE RIGHT TO DEVELOPMENT - Difa Ghiblartar Gastina; Irawati Handayani (Padjadjaran Journal of International Law, 2019)
AbstractDevelopment is one of the most common reasons to evict inhabitant forcibly. This happens because individuals or communities are placed as objects of development, causing the closure of participation space in development. In the perspective of human rights, development is claimed as a right, which every human being has the right to participate, contribute, and receive benefits for everything that results from development. This study aims to understand the perspective of the right to development towards forced evictions and the implementation od state obligation on the right to development at the national level. The study reveals that based on the principles in the right to development (such as holistic development;placement of humans as the central subject of development as well as participation in the development process) can protect individuals or communities from forced evictions. Futhermore, to ensure the fulfillment, state has key role to implement the right to development at the national level. Keywords: Forced Eviction, Human Rights, Right to Development. AbstrakPembangunan merupakan salah-satu alasan paling umum penyebab terjadinya penggusuran paksa. Hal ini dikarenakan individu atau masyarakat ditempatkan sebagai objek pembangunan yang menyebabkan tertutupnya ruang partisipatif dalam pembangunan tersebut. Dalam perspektif hak asasi manusia, pembangunan diklaim sebagai hak dimana setiap orang berhak untuk berpartisipasi, berkontribusi dan menerima manfaat hasil pembangunan. Penelitian ini bertujuan untuk mengetahui perspektif hak atas pembangunan terhadap penggusuran paksa, serta bagaimana kewajiban Negara dalam menerapkan hak tersebut ditingkat nasional. b Berdasarkan analisis terhadap prinsip-prinsip dalam hak atas pembangunana seperti pembangunan yang holistik; penempatan manusia sebagai subjek sentral dari pembangunan dan juga partisipasi dalam proses pembangunan dapat melindungi individu atau masyarakat dari penggusuran paksa. Untuk menjamin pemenuhannya, Negara dalam menerapkan hak atas pembangunan ditingkat nasional. Kata Kunci: Hak Asasi Manusia, Hak atas Pembangunan, Penggusuran Paksa.